The Influence of Tourist Perception and Motivation on Interest in Revisiting Beach Attractions Oysters Padang Pariaman Regency - Septiani, Shyndi; Yulihardi, Yulihardi; Amrullah, Amrullah (Adpebi Science Series, 2024)
Padang Pariaman Regency is a regency in West Sumatra Province, Indonesia. The capital city of Padang PariamanRegency is Parit Malintang. Through the Tourism Office, several tourism objects in Padang Pariaman Regencycontinue to be developed, because they have different values from other regional attractions, one of which is theOyster Beach tour in Ulakan Tapakis. Besides being a tourist attraction, it can also have an impact on local revenue(PAD) in the tourism sector.The type of research used in this research is associative research with a quantitative approach. The number ofrespondents in this study were 100 people. Collecting data by distributing questionnaires using a Likert scale. Thedata analysis technique used is multiple linear regression.Based on the results of partial research on interest in revisiting, the tcount value is 5.501 with df = 100-3= 97, so ttable is 1.660. Based on these data, tcount > t table or 5.501 > 1.660 and the value (sig = 0.000 < 0.05) sothat H2 is accepted and H0 is rejected. So it can be concluded that the motivation of tourists has a positive andsignificant effect on the interest in revisiting the Oyster Beach Tourism Object. The linear regression coefficient ofthe tourist perception variable partially on the interest in revisiting the value of tCount 2.137 with df = 100-3 = 97 thentTable 1.660. Based on these data, tCount > t Table or 2.137 > 1.660 and the value (sig = 0.035 < 0.05) so that H1 isaccepted and H0 is rejected. So it can be concluded that the perception of tourists has a positive and significant effecton the interest in revisiting the Oyster Beach Tourism Object.Based on the F test, it is known that the fCount IS 16.998 with df = 100-3 = 97, so fTable is 3,090. Based onthese data, fCount>fTable or 16.998> 3.090 and the value (sig = 0.000 <0.05) then H3 is accepted and H0 is rejected.So it can be concluded that the perception of tourists and the motivation of tourists simultaneously have a positiveand significant effect on the interest in revisiting the Oyster Beach Tourism Object. The value of the coefficient ofdetermination r-square is 26%, this means that the contribution of tourist perceptions and motivation of tourists tothe interest of repeat visits is 26% while the remaining 74% is influenced by other variables.